Improving students listening skill using Scooby Doo English subtitle movie - Chandra Nilawati; Rizky Lutviana (Journal of English Language Teaching and Learning (JETLE), 2022)
Listening skills tends to be ignored in the teaching and learning process because of several reasons including lack of facilities, lack of teacher competence and lack of students’ motivation. Therefore, teachers need to design creative instructional media as much as possible to address these issues. This study aimed at investigating the use of Scooby Doo English subtitle movie to improve the students’ listening skill. This study used applied Classroom Action Research (CAR) which consists of four major steps; planning, action, observation and reflection. The population of this research is 26 Senior High School students. There are three instruments used which include: test, observation, and questionnaire. Based on the findings, the improvement of the students’ listening skill was seen on the second cycle. On the second cycle, 23 or 88% of the students gained the score above the minimum mastery criterion. The students also actively followed the learning process. Students’ interest and motivation were also increased, they paid attention to the teachers’ explanation, asked question, responded the question, and accomplished the task. The students argued that the learning activities done using “Scooby Doo “The Case of Luna Ghost” English subtitle movie” could increase the students’ interest and motivation.